Analysis of Science Process Skills through Blended Learning in Science Subjects - Ari Ambarwati Umisaroh (CV. Tripe Konsultan, 2022)
This study aimed to determine the implementation of science process skills through blended learning during the Covid-19 pandemic. Blended learning is a structured learning process between face-to-face learning and online learning that is carried out separately or has its own time. The research method used is a qualitative approach. Data collection techniques using observation, interviews, and documentation. The main instrument in data collection is the researcher himself, for the auxiliary instruments, are observation guidelines, interview guidelines, and documentation. The data analysis procedure went through 3 stages namely 1) data reduction, 2) data exposure, and 3) conclusion drawing and verification. Data validity uses source and method triangulation by comparing data information obtained from interviews, observations and documentation. The subjects of this study were grade IV students, totaling 15 children. The results of data analysis show that the implementation of science process skills through blended learning during the Covid 19 pandemic can both help students and teachers in facilitating learning, and the results of the analysis of science process skills during the Covid 19 pandemic seem successful and have a good effect on students. The results of this study can be used as input and consideration for other researchers to conduct research with other science process skills analysis variables.